2017
DOI: 10.1136/bmjopen-2017-016857
|View full text |Cite
|
Sign up to set email alerts
|

Health education for patients with acute coronary syndrome and type 2 diabetes mellitus: an umbrella review of systematic reviews and meta-analyses

Abstract: ObjectivesThis umbrella review aimed to identify the current evidence on health education-related interventions for patients with acute coronary syndrome (ACS) or type two diabetes mellitus (T2DM); identify the educational content, delivery methods, intensity, duration and setting required. The purpose was to provide recommendations for educational interventions for high-risk patients with both ACS and T2DM.DesignUmbrella review of systematic reviews and meta-analyses.SettingInpatient and postdischarge setting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
35
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 80 publications
(105 reference statements)
2
35
0
Order By: Relevance
“…With the burgeoning of chronic diseases, such as diabetes mellitus and ischemic heart disease, associated with modifiable lifestyle risk factors, there is an urgent need to ensure that health communication optimizes the use of preventive health services (Berkman et al, ). Similarly, the key to the management of these chronic diseases, once established, is self‐management, which requires the person experiencing the condition to be able to understand and act upon information provided by health professionals (Liu, Shi, Willis, Wu, & Johnson, ). In a systematic review of interventions to reduce the effects of low literacy on health outcomes, most interventions focused on providing materials written in “simpler, easier‐to‐read prose” (Berkman et al, , p. 9).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…With the burgeoning of chronic diseases, such as diabetes mellitus and ischemic heart disease, associated with modifiable lifestyle risk factors, there is an urgent need to ensure that health communication optimizes the use of preventive health services (Berkman et al, ). Similarly, the key to the management of these chronic diseases, once established, is self‐management, which requires the person experiencing the condition to be able to understand and act upon information provided by health professionals (Liu, Shi, Willis, Wu, & Johnson, ). In a systematic review of interventions to reduce the effects of low literacy on health outcomes, most interventions focused on providing materials written in “simpler, easier‐to‐read prose” (Berkman et al, , p. 9).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, the key to the management of these chronic diseases, once established, is self-management, which requires the person experiencing the condition to be able to understand and act upon information provided by health professionals (Liu, Shi, Willis, Wu, & Johnson, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…[ 14 16 ] Individualized counseling or education, as well as a written plan of self-care on the basis of patient's personality, may improve patients’ motivation in adhering to dietary and life style modification measures. [ 17 ] This is supported via significant reductions in waist circumference, body mass index, and body weight, which are known to help diabetics control blood pressure, cholesterol, and blood sugar. [ 17 ] Moreover, a recent research suggested that the knowledge of diabetes was closely related to good control of blood glucose and medication adherence.…”
Section: Discussionmentioning
confidence: 99%
“…[ 17 ] This is supported via significant reductions in waist circumference, body mass index, and body weight, which are known to help diabetics control blood pressure, cholesterol, and blood sugar. [ 17 ] Moreover, a recent research suggested that the knowledge of diabetes was closely related to good control of blood glucose and medication adherence. [ 18 ] Despite the patients’ medication compliance is not evaluated in our current study, self-care programs and individualized education may improve the patients’ compliance with cardiovascular and hypoglycemia medications, so as to better control blood lipids, blood pressure, and blood glucose.…”
Section: Discussionmentioning
confidence: 99%
“…Semistructured interviews included specific questions (see Interview Schedule, online supplementary appendix ) and prompts to obtain more information, to clarify the points being made or for participants to add additional information. 34 The items within the interview schedule were derived from an umbrella review conducted by the research team, 35 with some modification following three initial interviews.…”
Section: Methodsmentioning
confidence: 99%